Bipartite Graphs Associated with 3 Uniform Semigraphs of Trees and its Topological Indices (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we have studied special class of bipartite graphs associated with 3 uniform semigraphs of path graph \( P_{m,1} \) and star graph \( S_{m,1} \) and estimated some topological indices such as Wiener index, Detour index, Circular index, Cut Circular index, vertex PI index and vertex Co-PI index of these graphs.
Keywords: Semi graph; Bipartite graphs associated with semigraphs; Wiener index; Detour index; Vertex PI index; Vertex Co-PI index